Anpassung an den Klimawandel als Herausforderung für Biosphärenreservate – das Beispiel Flusslandschaft Elbe-Brandenburg - Rannow, Sven; Warner, Barbara (Raumforschung und Raumordnung | Spatial Research and Planning, 2016)
Dealing with the effects of climate change poses new challenges for biosphere reserves as model regions for sustainable development. Although the impacts on ecosystems or landscapes can only be managed to a limited extent and are difficult to predict, the effects of climate change should be strategically addressed. Furthermore, it is necessary to involve numerous actors with various perspectives in the decisions that must be reached against a background of uncertain prognoses for the future. The paper uses the example of the UNESCO-Biosphere Reserve Elbe-Brandenburg River Landscape to illustrate the concrete fields of action that are emerging and the possible work phases involved in a planned approach to dealing with climate change. Various measures relevant to landscape water balance, vegetation, fauna and land use are demonstrated. On the Elbe, river basin management is particularly important. The discussion of possible strategic fields of action elucidates the roles that can be assumed by the administrations of biosphere reserves in a process of climate adaptation. The options and the extent to which biosphere reserves can develop into model regions for adaptation to climate change depend in practice on the capacities and expertise available.
Keywords: Adaptation strategies; Major protected areas; Biosphere reserves; River basin; Elbe; Land use